1999
DOI: 10.1007/s004420050754
|View full text |Cite
|
Sign up to set email alerts
|

Can pregnant lizards adjust their offspring phenotypes to environmental conditions?

Abstract: We exposed females of a highly placentotrophic viviparous scincid lizard (Pseudemoia pagenstecheri) to various environmental factors during pregnancy, and quantified the effects of these treatments on their offspring. The clear result was that the phenotypes of neonatal lizards can be substantially modified by the environment that their mother experiences during gestation. Restricting prey availability to the females reduced the size of their offspring. Limiting the females' basking opportunities delayed their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 42 publications
6
105
2
Order By: Relevance
“…Only a small number of studies have previously observed an increase in individual offspring size in response to predator cues [7,19,21,42]. Wild-radish plants (Raphanus raphanistrum) increase seed mass when attacked by caterpillars (Pieris rapae); however, this response might not be adaptive for the offspring [7].…”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of studies have previously observed an increase in individual offspring size in response to predator cues [7,19,21,42]. Wild-radish plants (Raphanus raphanistrum) increase seed mass when attacked by caterpillars (Pieris rapae); however, this response might not be adaptive for the offspring [7].…”
Section: Discussionmentioning
confidence: 99%
“…For example, offspring of Woodworthia 'Otago/ Southland' were proportionately shaped, in contrast with some lizard species in which cool-gestated offspring may have relatively short tails (Shine and Downes, 1999;Li et al, 2009) or relatively small or large mass (Shine and Harlow, 1993;While and Wapstra, 2009). In addition, at 2-3 months of age, geckos from different regimes were able to access a warm retreat as readily and to run by day as quickly.…”
Section: Effects Of Basking Regime and Delivery Mode On Offspring Phementioning
confidence: 93%
“…In reptiles, maternal effects have been found to have a substantial influence on offspring phenotype (Shine and Downes 1999). Hence the interaction between offspring phenotype and survival will be the result of both the offspring's genotype and its maternal environment.…”
Section: Outbreeding Depression?mentioning
confidence: 99%